2017
DOI: 10.3823/2490
|View full text |Cite
|
Sign up to set email alerts
|

The Irritating Effects Of Exposure To Formaldehyde In User Students Of The Human Anatomy Laboratory

Abstract: Formaldehyde (FA) is commonly used in cadaver fixation for years. FA vapors are released during the dissection process and macroscopic study of preserved anatomical pieces, raising their concentration in the Anatomy laboratory, causing greater exposure for students and teachers. Therefore, the objective of this study was to investigate toxic reactions in 37 students, through a questionnaire, produced by exposure to FA used for preservation of cadaveric material used in Anatomy, Morphofunctional Department, Fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
1
1
1
1
Order By: Relevance
“…Some individuals were highly sensitive to the FA while others were more resistant and had no reaction to the same level of exposure [ 40 ]. In our study, the most frequent complaint reported by the exposed students was the unpleasant smell (78.8%) ( Figure 9 ), and this occurrence is consistent with some previous studies which also reported this symptom as the most predominant one at 68% [ 21 ], 80% [ 41 ], 77% [ 42 ], 57.5% [ 35 ], 91.2% [ 43 ] and, 70.3% [ 44 ]. This common finding simply reflects that FA exposure is mainly by inhalation during the dissection sessions.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Some individuals were highly sensitive to the FA while others were more resistant and had no reaction to the same level of exposure [ 40 ]. In our study, the most frequent complaint reported by the exposed students was the unpleasant smell (78.8%) ( Figure 9 ), and this occurrence is consistent with some previous studies which also reported this symptom as the most predominant one at 68% [ 21 ], 80% [ 41 ], 77% [ 42 ], 57.5% [ 35 ], 91.2% [ 43 ] and, 70.3% [ 44 ]. This common finding simply reflects that FA exposure is mainly by inhalation during the dissection sessions.…”
Section: Resultssupporting
confidence: 91%
“…This finding is worth considering by the educational system because it can impair students’ learning progress [ 46 ]. In a study from Thailand, however, the most common clinical symptom was general fatigue (87.8%) [ 32 ], which was less frequently reported in other studies at 38.5% [ 36 ], 36% [ 21 ] and 21.8% [ 44 ], as well as 9.4% in our study.…”
Section: Resultscontrasting
confidence: 77%
“…Sua composição é de carbono carbonílico ligado a dois hidrogênios (-HCHO), gerados da oxidação do metanol (IARC, 2006). É, porém,um produto tóxico, com elevado potencial cancerígeno (OHMICHI et al, 2006), de modo particular para casos de contato diário por períodos prolongados e com frequência em sessões de dissecação e estudo macroscópico, como no caso de pesquisadores, docentes, e técnicos de laboratório ou manipuladores industriais (VIEIRA et al, 2013;NIELSON;WOLKOFF, 2010;MERK;SPEIT, 1998;ONYIJE;AVWIORO, 2012;DE LUCENA et al, 2017;DE PAULA et al, 2018;ONYEKA et al, 2018;YAGER et al, 1986) 2014).…”
Section: Discussionunclassified
“…The permissible occupational exposure limit for formaldehyde is 0.75 ppm, measured as an 8-h time-weighted average (OSHA, 2011). However, previous studies have shown the formaldehyde concentration varying between 0.75 and 4 ppm inside anatomy laboratories, embalming rooms, and personal sampling rooms (Albertini and Kaden, 2017;de Lucena et al, 2017). In industry, the concentration of formaldehyde exposure is reported between 0.04 and 3.48 ppm, with wood production workers, mortuary employees, and firefighters exposed to the highest concentrations (Dan et al, 2020).…”
Section: Introductionmentioning
confidence: 98%